1994
DOI: 10.1111/j.1600-0447.1994.tb05899.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive therapy with schizophrenic patients: conceptual basis, present state, future directions

Abstract: Schizophrenia may nowadays be most readily understood as a systemic disorder in which changes in the brain structure underlie individual cognitive abnormalities which for their part interact with environmental factors at the onset of the illness and during its course. From this, one may deduce the rationale for cognitive therapy for schizophrenic patients. Existing approaches may be systemised as direct, indirect and combined procedures. The latter are based on the assumption of the pervasive effects of elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 37 publications
0
14
0
2
Order By: Relevance
“…An earlier, atheoretical, problem-solving approach that we tested (major role therapy) (17,25) proved useful for better-recovered patients but had negative effects for certain vulnerable or unmedicated patients. In recent years, the integrated psychological treatment of Brenner et al (26), a sequenced application of basic cognitive remediation and social skills training or problem-solving techniques, has been evaluated in six completed (27) and two ongoing (28,29) trials. Published results cited improvement in attention and symptoms, but less apparent effects were observed on higher-order cognitive functioning and social adjustment.…”
mentioning
confidence: 99%
“…An earlier, atheoretical, problem-solving approach that we tested (major role therapy) (17,25) proved useful for better-recovered patients but had negative effects for certain vulnerable or unmedicated patients. In recent years, the integrated psychological treatment of Brenner et al (26), a sequenced application of basic cognitive remediation and social skills training or problem-solving techniques, has been evaluated in six completed (27) and two ongoing (28,29) trials. Published results cited improvement in attention and symptoms, but less apparent effects were observed on higher-order cognitive functioning and social adjustment.…”
mentioning
confidence: 99%
“…This disorder may have a very heterogeneous clinical presentation and course, but frequently leads to a high degree of disability in several daily life activities (Meise and Fleischhacker 1996). Several intervention programs have been designed and 'applied to patients with schizophrenia in order to improve their social functionihg and reduce their disability (Garety et al 1994;Hodel and Brenner 1994;Kuipers et al 1998;Penades 2002). However, patients with schizophrenia still show high degrees of social disability (Usall et al 2002;Ochoa et al 2003;Villalta-Gil et al 2006).…”
mentioning
confidence: 99%
“…A controlled study in which one group of patients began the study in the normal IPT order was compared to a group of patients who started with the social intervention before moving on to the cognitive exercises. This study did not confirm the assumption of the pervasive effects of elementary cognitive dysfunction at the levels of open behaviour (116). Hodel and Brenner (1 16) conclude that 'the therapeutic procedures employed in the cognitive subprogrammes do not specifically meet the needs of schizophrenic patients' (p. 1 12).…”
Section: Previous Studies On Cognitive Remediation In Schizophrenic Pmentioning
confidence: 73%
“…A few clinical studies conducted in the late 1960s and 1970s all reported encouraging results. Spring and Radvin (115) and Hodel and Brenner (116) have reviewed these early studies. After this promising beginning, the research has lain dormant for more than a decade.…”
Section: Previous Studies On Cognitive Remediation In Schizophrenic Pmentioning
confidence: 99%